2017
DOI: 10.1021/acs.jmedchem.7b00407
|View full text |Cite|
|
Sign up to set email alerts
|

Dipicolinic Acid Derivatives as Inhibitors of New Delhi Metallo-β-lactamase-1

Abstract: The efficacy of β-lactam antibiotics is threatened by the emergence and global spread of metallo-β-lactamase-(MBL) mediated resistance, specifically New Delhi-Metallo-β-lactamase-1 (NDM-1). Utilizing fragment-based drug discovery (FBDD), a new class of inhibitors for NDM-1 and two related β-lactamases, IMP-1 and VIM-2, was identified. Based on 2,6-dipicolinic acid (DPA), several libraries were synthesized for structure-activity relationship (SAR) analysis. Inhibitor 36 (IC50 = 80 nM) was identified to be highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
154
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 133 publications
(161 citation statements)
references
References 65 publications
3
154
0
1
Order By: Relevance
“…[28] Also during the time of this study,as tructure of 2 in complex with IMP-1 (PDB ID:5 HH4) was reported. [28] Also during the time of this study,as tructure of 2 in complex with IMP-1 (PDB ID:5 HH4) was reported.…”
Section: Uv/vis Spectroscopymentioning
confidence: 95%
See 4 more Smart Citations
“…[28] Also during the time of this study,as tructure of 2 in complex with IMP-1 (PDB ID:5 HH4) was reported. [28] Also during the time of this study,as tructure of 2 in complex with IMP-1 (PDB ID:5 HH4) was reported.…”
Section: Uv/vis Spectroscopymentioning
confidence: 95%
“…[22,47] The inclusion of captopril to the sample resultsi nl arge changes in the ligand field transitions, and an increase in the LMCT band. [28] Incubation of CoCo-NDM-1 with compounds 1-4 and DPAresulted in ar eductiono fa bsorbance at 500-650nm( Figure 4), which indicates that Co II is being removed from the active site to varying degrees.C ompound 2 appears to remove the most Co II ,followed by compound 1,DPA, 3,and then 4.The findings with CoCo-NDM-1 are wholly consistent with the equilibrium dialysis results. [48] Incubation of CoCo-NDM-1 with EDTAr esulted in as ignificant decrease of the LMCT and ligand field peaks, indicating that EDTA strips the metal from NDM-1.…”
Section: Uv/vis Spectroscopymentioning
confidence: 97%
See 3 more Smart Citations